INFLUENCE OF THE CHARACTERISTICS OF ROAD TRAFFIC ON THE DRIVER’S FUNCTIONAL STATE: Array - and (Municipal economy of cities. Series: «Economy science», 2018)
The article presents the study of the work of the driver in the traffic flow in the city conditions. The change of ergonomic characteristics on the city route is considered. The regularities of changing the functional condition of the driver on the route with consideration of physiological parameters are presented. To estimate the influence of the conditions of movement on the characteristics of the work of the driver, the indicator of traffic delays and the technical speed of the route. The dependencies of changing the functional condition of the driver on the technical speed on the route are presented. To determine the functional state of the driver, indicators of the galvanic skin response and shift of the heart rate of the driver are used. It is suggested to change the leather-galvanic reaction on separate sections of the route, taking into account the change in the area index. It is established that the driver’s greatest emotional stress corresponds to those sections of the route where there are unsatisfactory traffic conditions. The shift in the heart rate, on the contrary, increases on the sections of the route with an average level of traffic load, as well as in those places on the road where there are dangerous braking and stressful situations. Considered the influence of traffic factors on the emotional state of the driver. In the process of driving, the driver is faced with different situations on the road: pedestrians, dense traffic, traffic in a traffic jam, etc. The reasons listed are the result of the mental state, driver fatigue, lack of experience and driving skills. It is important to know the factors that influence driver errors in stressful driving situations and the nature of changes in the driver’s condition. When driving, the driver must maintain an optimal emotional state for a long time. Under the optimum condition of the driver, the process from the perception of information to the implementation of actions determines the response time of the driver. From the state of the driver depends on the error when driving. The choice of optimal driving modes will allow the driver to avoid stress while driving. Keywords: Human factor, traffic flow, technical speed, traffic delays, functional state of the driver.